“I’ve found more difficulties than I expected to”: Raising questions from field experience - Brandão, Ana Maria (Qualitative Sociology Review, 2009)
Sociology students in Portugal have usually been taught methodology and epistemology in a classical, scholastic way. If students are provided with practical contact early on, this can help them to better understand and apply theoretical concepts conveyed through lectures. During their last graduate year, Sociology students of the University of Minho are expected to design a full research project and to conduct exploratory research, completed by the last semester, and this includes either a residence period or a research seminar. To ensure this works well, methodology units are organised on a weekly basis, according to two types of classes: 1) theoretical and 2) theoretical-practical, with the purpose of gradually enabling students to develop the competencies they will need to graduate. Focusing on the teaching experience of qualitative methodologies, and using as an example the teaching of observation techniques, the purpose of this article is to illustrate the advantages of offering the students early contact with the “field”, and prepare them for future full-scale research. These advantages are acknowledged by students, as evidenced in their written evaluations of their field experiences. However, it is important to note that this type of learning is most fruitful when students have been previously trained in the use of the written language – namely aiming to develop their ability to describe – and social theories.